On Atheists and Bonobos A Conversation with Frans de Waal. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Frans de Waal, the Charles Howard Candler Professor of Psychology at Emory University and the Director of the Living Links Center at Yerkes National Primate Research Center. Frans de Waal is renowned for his work on the behaviour and social intelligence of primates. This thought-provoking conversation examines fascinating questions such as: Are we born with an innate sense of ""the good""? Do we learn from others what is ""wrong""? Does religion determine, or is it a result of, morality?This carefully-edited book i.